Mental, physical or combined practice in motor performance and learning: a meta-analytical response - Jiménez Díaz, Judith (2022)
Practice is a key element in the process of acquiring motor skills, because it facilitates learning. This practice can be of either of two types—physical or mental. The objective of the present study is to determine the extent of effect of physical practice (PF), mental practice (PM) and combined practice (PC) throughout the process of acquisition and retention in the performance of motor skills, using a meta-analytical approach and the analysis of possible moderating variables. The random effect model was used to calculate the extent of the effect (TE). A total 24 studies were included, and a total of 150 TE was obtained, separated in four groups. In the phase of acquisition, it was found that the PF (TE = 1.75; n = 36; IC = 0.96,3.55; Q = 113; I2 = 92%), the PM (TE = 0.80; n = 36; IC = 0.50,1.09; Q = 108; I2 = 74%) and the PC (TE = 1.78; n = 22; IC = 1.39,2.18; Q = 167; I2 = 79%) improved their performance; in addition, the control group (GC) improved the performance in acquisition (TE = 0.18; n = 22; IC = 0.02,0.35; Q = 19; I2 = 0%). A meta-regression indicated that only physical, mental and combined practice significantly predict the TE. In the retention phase, neither the PF (TE = -0.97; n = 9; IC = -0.41,0.02; Q = 12; I2 = 29%), the PM (TE = 0.62; n = 6; IC = -0.19,1.45; Q = 22; I2 = 83%), the PC (TE = -0.01; n = 14; IC = -0.26,0.25; Q = 23; I2 = 46%) or the GC (TE = -0.15; n = 5; IC = -0.75,0.44; Q = 11; I2 = 66%) showed a significant change. Possible moderating variables were analyzed. The results suggest that the three types of practice improve performance in the acquisition phase, while in the retention phase they help to keep what has been learned. The PM does not replace PF; however, PF can be complemented with PM under some conditions.